2022
DOI: 10.1039/d2tc02995b
|View full text |Cite
|
Sign up to set email alerts
|

Zn-derived ligand engineering towards stable and bright CsPbI3 nanocrystals for white emitting

Abstract: Lead-halide perovskite nanocrystals (NCs), such as red-emitting CsPbI3, have gained significant attention due to their promising applications such as display backlights, light emitting devices, and lasers. However, it is still...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 44 publications
2
14
0
Order By: Relevance
“…The addition of SDBS ligands reduced the particle size of CsPbI 3 NCs from 17.15 to 16.7 nm, indicating that SDBS ligands inhibit the growth of CsPbI 3 NCs and enhance the quantum confinement effect. The HRTEM images in Figure c,g show that all samples have clear lattice fringes, and the lattice spacing of 0.31 nm corresponds to the (200) plane of α-CsPbI 3 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of SDBS ligands reduced the particle size of CsPbI 3 NCs from 17.15 to 16.7 nm, indicating that SDBS ligands inhibit the growth of CsPbI 3 NCs and enhance the quantum confinement effect. The HRTEM images in Figure c,g show that all samples have clear lattice fringes, and the lattice spacing of 0.31 nm corresponds to the (200) plane of α-CsPbI 3 …”
Section: Resultsmentioning
confidence: 99%
“…Figure 1a,e 1c,g show that all samples have clear lattice fringes, and the lattice spacing of 0.31 nm corresponds to the (200) plane of α-CsPbI 3 . 39 The optical properties of CsPbI 3 and SDBS-CsPbI 3 were characterized next. Figure 2a,b shows the PL spectra and UV− vis absorption spectra of CsPbI 3 NCs synthesized with different molar ratios of SDBS ligands.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…However, under the same condition, pure CsPbBr 3 degraded and showed no PLQY after 30 days. Similarly, Shi et al 154 studied the (1-dodecanethiol) DDT-Zn:CsPbI 3 NCs under UV light irradiation and five cycles of heating–cooling treatment from 20 to 150 °C. It was found that DDT-Zn:CsPbI 3 retained 90% and 85% of initial PL intensity after exposure to UV irradiation for 110 min and five cycles of heat treatment, respectively, showing improved performance than that of pure CsPbBr 3 (which retained only 25% after 40 min of UV irradiation and almost quenched after five cycles of heat treatment).…”
Section: Perovskite Materials Degradationmentioning
confidence: 99%
“…Semiconductor quantum dots (QDs) has been considered an interesting candidate in g-C 3 N 4 modification due to its relatively narrower band gap and its absorption band that is able to cover the whole visible region by composition adjustment. [112][113][114][115][116][117][118] The QDs decorated g-C 3 N 4 nanosheets based type II heterostructure thus often possess improved light absorption and charger carrier separation efficiency. For example, Raziq and coworkers reported a CdSe QDs modified thin porous P-doped g-C 3 N 4 (P-CN) nanosheets for water splitting application, as shown in the TEM images in Figure 6a to c. [119] The absorbance spectra of the constructed CdSe QDs modified g-C 3 N 4 composites (sample 4CdSe/P-CN in Figure 6d) confirmed the significantly enhanced visible-light absorption range (to around 700 nm).…”
Section: Type II G-c 3 N 4 Nanosheets Heterostructure Nanoarchitectonicsmentioning
confidence: 99%